Decreased Gray Matter Volume of Right Inferior Parietal Lobule Is Associated With Severity of Mental Disorientation in Patients With Mild Cognitive Impairment - Oishi, Ayame; Yamasaki, Takao; Tsuru, Ayako; Minohara, Motozumi; Tobimatsu, Shozo (Frontiers in Neurology, 2018)
Background: Mental disorientation in time, space, and with respect to people is common in patients with Alzheimer’s disease (AD) and mild cognitive impairment (MCI). Recently, a high resolution functional MRI (fMRI) study revealed that the inferior parietal lobule (IPL) and precuneus are important regions related to mental orientation in healthy individuals. We hypothesized that the IPL and/or precuneus are crucial regions for mental disorientation in patients with amnestic MCI (aMCI). Therefore, our aim was to assess our hypothesis in these patients using voxel-based morphometry (VBM). Methods: Fifteen patients with aMCI participated. The Neurobehavioral Cognitive Status Examination (COGNISTAT) as well as the Mini-Mental State Examination (MMSE) were used to evaluate mental disorientation. Subsequently, we used VBM analysis to identify brain regions that exhibited gray matter (GM) volume loss associated with mental disorientation. Based on our hypothesis, four brain regions (bilateral IPLs and precuneus) were selected as regions of interest (ROIs). Results: We found a significant decreased GM volume in the right IPL, which was correlated with lower orientation scores on the COGNISTAT. In contrast, GM volume in other ROIs did not show a significant positive correlation with mental disorientation. Regarding the MMSE, no significant reduction in GM associated with decline in orientation were observed in any ROI. Conclusion: We found the significant relationship between low GM volume in the right IPL and severity of mental disorientation on the COGNISTAT scores but not on the MMSE scores. This suggests that the COGNISTAT is useful for exploring mental disorientation in aMCI.